An In Situ Oxidative Polymerization Method to Synthesize Mesoporous Polypyrrole/MnO2 Composites for Supercapacitors - Yan Song; Yangbo Dong; Wei Li; Zhengwen Tan; Pingfei Ma; Guibin Wang; Xuefeng Li (Molecules)
Manganese dioxide (MnO2) shows great potential in the field of electrochemical performance. But its poor conductivity, easy dissolution in electrolytes and undesirable ionic accessibility hinder its application. The construction of mesoporous polypyrrole/manganese dioxide (PPy/MnO2) composites can effectively alleviate these problems. Herein, an in situ oxidative polymerization method is developed to synthesize mesoporous PPy/MnO2 composites. In this method, Pluronic P123 and pyrrole monomers are co-assembled on the surface of MnO2. MnO2 is used as an oxidation initiator to polymerize pyrrole under acidic conditions and as a substrate for a uniform coating of PPy. The obtained composites, with a large electrochemical effective area, more reaction sites and good structural stability have better capacitor performance (182.8 F g−1), higher than MnO2 (116.6 F g−1) at the same current density. This method provides a meaningful reference for the development of mesoporous PPy/MnO2 supercapacitor materials.